1971
DOI: 10.2514/3.30367
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic limitations on the diffusional control theory of the ablation rate of carbon.

Abstract: Nomenclature h= Planck constant k = Boltzmann constant m = molecular mass of oxygen m = mass-loss or reaction rate, g/cm 2 sec POZ = oxygen pressure, atm P i2 = stagnation pressure of air adjacent to the surface, atm R = gas constant, 1.987 cal/mole °K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…In addition, carbon erosion by oxygen has been the subject of Refs. [11][12][13][14][15][16][17][18][19]. This data has not been widely applied to rocket motor design because the data was not correlated into a useful form, or the data did not provide sufficient information about the complex interactions of reactants and inhibitors such as HC1 or CO.…”
Section: Reaction Characteristicsmentioning
confidence: 99%
“…In addition, carbon erosion by oxygen has been the subject of Refs. [11][12][13][14][15][16][17][18][19]. This data has not been widely applied to rocket motor design because the data was not correlated into a useful form, or the data did not provide sufficient information about the complex interactions of reactants and inhibitors such as HC1 or CO.…”
Section: Reaction Characteristicsmentioning
confidence: 99%
“…This behaviour can be seen upon close inspection for some of the data in Figure 2.1. As a consequence of this, Maahs [46] noted that the maximum mass loss rate due to oxidation will be kinetic-controlled and not diffusion-limited for a wider range of conditions than was previously thought.…”
Section: Oxidationmentioning
confidence: 86%
“…The exact terminology used varies between authors [46,69,72], although the same trends are observed. In the kinetic-limited regime, also known as reaction limited or chemistry limited, the surface temperature and flow conditions are sufficient to allow surface reactions to occur and are limited by the reaction rates.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations